What economists can learn from "The power of us: Harnessing our shared identities for personal and collective success" by Jay J. van Bavel and Dominick J. Packer - Daniela Grieco (Games, 2022)
Social identity theory has become increasingly important for economists. I discuss the contribution of Van Bavel and Packer's "The Power of Us" in light of what economists (especially experimental ones) can learn from their research.
Keywords: 330; experiments; ingroup bias; social identity